2022
DOI: 10.1111/desc.13337
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver monitoring, but not caregiver warmth, is associated with general cognition in two large sub‐samples of youth

Abstract: Individual differences in cognitive abilities emerge early during development, and children with poorer cognition are at increased risk for adverse outcomes as they enter adolescence. Caregiving plays an important role in supporting cognitive development, yet it remains unclear how specific types of caregiving behaviors may shape cognition, highlighting the need for large-scale studies. In the present study, we characterized replicable yet specific associations between caregiving behaviors and cognition in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…This finding adds to the long-established protective effect of monitoring on mental health and academic resilience and the prevention of risk-taking behaviors, especially for youth living in unsafe or under-resourced neighborhoods (Ozer et al, 2017). A recent paper with participants in the ABCD study identified that a greater degree of caregiver monitoring, but not warmth, mediated the association between youths' household income and general cognitive ability scores (Keller et al, 2023). Given that CR youth had significantly more neighborhood disadvantage than CV youth, a greater level of caregiver monitoring may reflect differences in neighborhood violence and crime that necessitate a greater level of supervision to lessen the risk of harm (Ozer et al, 2017).…”
Section: Prediction Of Ser-dependent Cognitive Profiles: Resilience V...mentioning
confidence: 75%
“…This finding adds to the long-established protective effect of monitoring on mental health and academic resilience and the prevention of risk-taking behaviors, especially for youth living in unsafe or under-resourced neighborhoods (Ozer et al, 2017). A recent paper with participants in the ABCD study identified that a greater degree of caregiver monitoring, but not warmth, mediated the association between youths' household income and general cognitive ability scores (Keller et al, 2023). Given that CR youth had significantly more neighborhood disadvantage than CV youth, a greater level of caregiver monitoring may reflect differences in neighborhood violence and crime that necessitate a greater level of supervision to lessen the risk of harm (Ozer et al, 2017).…”
Section: Prediction Of Ser-dependent Cognitive Profiles: Resilience V...mentioning
confidence: 75%